2020
DOI: 10.21272/sec.4(2).90-98.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Connexus of Management by Objectives and Organisational Performance: Evidence from Tuyil Pharmaceutical Limited, Ilorin

Abstract: In modern conditions, the competitiveness of enterprises largely depends on the ability of management to ensure the necessary economic efficiency of operational activities, achieving strategic and tactical goals, rational use of labor, financial and material resources, which determines the relevance of research on innovative approaches to management “my goals”. The article substantiates that this concept is focused on increasing productivity through clear guidelines for each employee of the organization and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to Brimah, Bamidele and Rabiu (2020), the competitiveness of religious organisations in modern conditions is largely dependent on management's ability to ensure the required economic efficiency of operating operations, the achievement of strategic and tactical objectives, the reasonable use of labour, financial and material capital. This defines the importance of research on novel approaches to human skills to objectives-based management.…”
Section: Proceedings Of Adved 2020-6th International Conference On Admentioning
confidence: 99%
“…According to Brimah, Bamidele and Rabiu (2020), the competitiveness of religious organisations in modern conditions is largely dependent on management's ability to ensure the required economic efficiency of operating operations, the achievement of strategic and tactical objectives, the reasonable use of labour, financial and material capital. This defines the importance of research on novel approaches to human skills to objectives-based management.…”
Section: Proceedings Of Adved 2020-6th International Conference On Admentioning
confidence: 99%
“…Lahmini et al (2020) analysed the relation between immaterial capital in Moroccan companies listed on the Casablanca Stock exchange and their performance (market capitalization, ROA). Brimah et al (2020) studied the influence of innovative management approaches on pharmaceutical company's' performance in Nigeria. Shasha (2021) examined the effect of R&D expenses on profitability (ROA, Profit Margin) of Chinese listed companies from 2015 to 2017 and confirmed that the intensity of investment in R&D positively affects the profitability of enterprises.…”
Section: Introductionmentioning
confidence: 99%